The Pengaruh Penggunaan E-Payment terhadap Perubahan Perilaku Konsumsi: Studi Kasus Mahasiswa Fakultas Keislaman Universitas Trunojo Madura: E-payment, Marketplace, Perilaku Konsumtif - faros burneh sherbu; Moh. Karim (Accounting Journal of Ibrahimy (AJI), 2025)
At this time, technological developments have a major impact on human life in various fields, one of which has an impact on the economic sector, the purpose of this study aims to determine the effect of e-payment on consumer behavior through purchases in the marketplace. The method used in this research is quantitative, relying on the distribution of questionnaires with several questions contained in geogle form media and supporting articles related to the research theme. The results of the study prove that the existence of one of the products in the current economic field, namely e-payment, greatly affects the consumptive behavior of consumers. Because in its application e-payment is very effective and makes it easier for buyers and sellers to make a transaction.